2020
DOI: 10.1111/cdev.13388
|View full text |Cite
|
Sign up to set email alerts
|

Gender Discrimination, Perceived School Unfairness, Depressive Symptoms, and Sleep Duration Among Middle School Girls

Abstract: The current study examines how gender discrimination by adults in school is linked with depressive symptoms and sleep duration over time in middle school. The main goal is to test one psychological mechanism that can account for such associations: perceived school unfairness. Relying on a racially-ethnically diverse sample of girls (N = 2,718, M age = 13.01, SD age = 0.39) from 26 middle schools, multilevel mediation analyses revealed that girls who experienced school-based gender discrimination by an adult in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 68 publications
0
14
0
Order By: Relevance
“…For example, Gibbons, O'Hara, Stock, Gerrard, Weng, & Wills (2012) showed that discriminatory experiences of African-American adolescents increased anger and impulsivity. Another study shows how girls' experience of gender discrimination by middle school staff predicts increased depression and decreased sleep (Bell & Juvonen, 2019). Sleep deprivation as well as poor quality sleep, in turn are related to increased threat and anxiety (Talbot, McGlinchey, Kaplan, Dahl, & Harvey, 2010) and lower academic performance (Dewald, Meijer, Oort, Kerkhof,, & Bögels, (2010).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Gibbons, O'Hara, Stock, Gerrard, Weng, & Wills (2012) showed that discriminatory experiences of African-American adolescents increased anger and impulsivity. Another study shows how girls' experience of gender discrimination by middle school staff predicts increased depression and decreased sleep (Bell & Juvonen, 2019). Sleep deprivation as well as poor quality sleep, in turn are related to increased threat and anxiety (Talbot, McGlinchey, Kaplan, Dahl, & Harvey, 2010) and lower academic performance (Dewald, Meijer, Oort, Kerkhof,, & Bögels, (2010).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple aspects of gender and gender socialization shape health and wellbeing over the life course ( Snow, 2008 ). For example, an egalitarian view of gender roles is associated with lower conduct problems for both boys and girls ( King et al, 2019 ), and girls in middle-school who experience gender discrimination by an adult in their school report higher depression and worse sleep ( Bell and Juvonen, 2020 ). In adolescence, girls who uphold rigid beliefs about femininity report low rates of sexual self-efficacy and a greater propensity for sexual risk taking ( Impett et al, 2006 ).…”
Section: Rationale For Assessing Gender In the Abcd Studymentioning
confidence: 99%
“…For instance, English et al (2014) found that racial discrimination was associated with depression among Black girls. Regarding the impact of gender discrimination on depressive symptomatology, perceived gender discrimination from teachers was associated with perceiving the environment as inequitable and higher depressive symptomatology among a racially and ethnically diverse sample of adolescent females (Bell & Juvonen, 2020).…”
Section: Racial and Gender Discrimination In Classroomsmentioning
confidence: 99%